PECULIARITIES OF KNOWLEDGE OF NATURE IN THE EARLY STAGES OF SOCIAL DEVELOPMENT - Sidorkina, Olena (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2022)
Introduction. An important place in understanding modern global environmental problems is given to the study of the content and nature of scientific knowledge about nature, human interaction with it, the methods served as a methodological basis for understanding and gaining new knowledge of natural processes. The study of the problems of the scientific knowledge formation in the field of nature and society interaction in the historical aspect allows a deeper understanding of the current state of the issue and contributes to the improvement of its methodological foundations. The aim and tasks of this article are aimed at the analysis of the features of the formation and nature of knowledge of nature at the early stages of social development. Research methods. The methodological basis of the study is primarily the theoretical foundations of the dialectical approach in understanding the interaction between nature and society, in particular, the mediation of such interaction through human labor, as well as the theoretical legacy of philosophical research on the problems of science, the specifics of the formation of scientific knowledge. Research results. . The characteristic features of knowledge of nature and its interaction with man inherent in that phase of development of the spiritual culture of society are: a) the effect of "dissolution" in nature for primitive man with the formation of a figurative and emotional perception of the world, anthropomorphization of the forces of nature and its general spiritualization; b) the integration of nature into the structure of the universe without separating it into a separate object of cognition or understanding it as an expression of the abstract essence of man, cosmology in comprehending the world; c) holistic "feeling" of nature and contemplation in its understanding as the basis for cognition of its harmony and perfection; d) the presence in the system of cognition of nature as an obligatory component of the supernatural substance; e) knowledge about nature as part of a system of religious beliefs; f) the interweaving of elements of rational and mythological knowledge, their indivisibility. Discussion. The worldview aspect of the mythological understanding of the relationship between nature and man, the explanation of natural processes and phenomena can be understood through the scientific concept of religious consciousness in general and its characteristic features, cognitive features of the human mind. One of the ways to study the issues of interaction between nature and society is to analyze the characteristics of individual and social labor as a mediating process between man and nature. At the heart of the primitive mythological understanding of nature is also a specific type of knowledge about the nature of man's relationship with the world around him. Соnclusion. The characteristic features of knowledge about nature and the interaction of a person with it, inherent in this phase of development of the spiritual culture of society, are contemplation and dissolution of the cognizing subject in nature, anthropomorphization of the forces of nature, their spiritualization, cosmology in comprehending the world. The origins of such a close interweaving of various forms of spiritual culture and social consciousness of primitive man, the indivisibility of his knowledge of nature and the cognitive sphere as a whole, lie in the indivisibility of social life itself. The similar nature of the relationship to nature and the methods of its cognition reflected the level of development of the material productive forces of society, culture, cognitive activity, general living conditions